2004
DOI: 10.1021/bp049725n
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biologically Active Bacillus anthracis Edema Factor in Escherichia coli

Abstract: Anthrax is caused by the gram-positive spore-forming bacterium Bacillus anthracis. The anthrax toxin consists of three proteins, protective antigen (PA), lethal factor (LF), and edema factor (EF). PA facilitates the translocation of LF and EF into the cytosol of mammalian cells. LF is thought to be a zinc-dependent metalloprotease that results in death. EF is a calmodulin- and calcium-dependent adenylate cyclase that causes edema upon entrance into the cytosol by elevating the cAMP levels in cells. Previous ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…It is very likely, however, that hypotension with ETx is, in part, related to the adenyl cyclase activity of EF [6,28]. The recombinant ETx preparation investigated stimulated adenyl cyclase in CHO-K1 cells, just as ETx prepared from live B. anthracis did previously [6,23]. In the present in vitro studies, the efficient delivery of EF to the cytosol by PA binding caused rapid increases in levels of intracellular cAMP.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is very likely, however, that hypotension with ETx is, in part, related to the adenyl cyclase activity of EF [6,28]. The recombinant ETx preparation investigated stimulated adenyl cyclase in CHO-K1 cells, just as ETx prepared from live B. anthracis did previously [6,23]. In the present in vitro studies, the efficient delivery of EF to the cytosol by PA binding caused rapid increases in levels of intracellular cAMP.…”
Section: Discussionmentioning
confidence: 62%
“…Toxin components (PA, LF, and EF) were recombinant proteins prepared and purified from Escherichia coli by standard chromatographic techniques described elsewhere [22][23][24]. Endotoxin levels were !0.1 EU/mg protein for each component as based on testing with a limulus amebocyte lysate assay.…”
Section: Animalmentioning
confidence: 99%
“…The role of the adenylate cyclase activity for the adjuvanticity remains to be elucidated. In this regard, the EF used in our studies contains a S447N mutation that could account for its recently reported 20-fold lower ability to induce cAMP when compared with recombinant native EF protein (33). Several mutants of both CT and LT-I, which are devoid of ADP-ribosyl transferase activity, were shown to retain their mucosal adjuvant activity and the ability to promote high mucosal IgA Ab responses.…”
Section: Discussionmentioning
confidence: 97%
“…173) and was produced in a recombinant strain of B. anthracis using an expression plasmid constructed by S. H. Leppla. This EF protein contains a S447N mutation and was shown to display ϳ20-fold less enzymatic activity than the native EF (33). Controls included mice nasally immunized with OVA plus 1 g of CT (List Biological Laboratories).…”
Section: Immunizationmentioning
confidence: 99%
“…In all experiments except for experiment 7 (comparison of Sprague-Dawley and Lewis rats), toxin components (protective antigen, lethal factor, and edema factor) were recombinant proteins prepared from Escherichia coli as previously described (5,13,20). Edema toxin and lethal toxin were composed of edema or lethal factors, respectively, with protective antigen in ratios of 1:2 on the basis of weight (the molecular weights of all three components are very similar).…”
Section: Toxin and Treatmentsmentioning
confidence: 99%